Integration of risks from multiple hazards into a holistic ALARA/ALARP demonstration. (6th December 2017) - Bryant, P A; Croft, J; Cole, P
Abstract: The principle of As Low As Reasonable Achievable (ALARA) stems from the field of radiological protection. In the UK, this principle has been incorporated into the Health and Safety at Work Act 1974 and rather than applying solely to radiological hazards, applies to all hazards in totality. Given that the current methods for assessing hazards are somewhat isolated, in that one hazard is assessed independently of another, it can be challenging to ensure a truly holistic view of the risks, and demonstrate they have been reduced to ALARA or As Low As Is Reasonably Practicable (ALARP) as required in the UK regulatory regime. The following paper presents a proposed framework for the integrated assessment of risks from multiple hazards. In addition, it presents an overview of some of the key challenges that may be encountered when producing a holistic ALARA demonstration.